Sexuality and Gender Neutral for Men in the Perspective of Maqashid Al-Shari'ah - Rafik Patrajaya; Aris Sunandar Suradilaga; Anas Maulana (Alhurriyah, 2025)
This paper explores the development of contemporary gender discourse that seeks to deconstruct traditional masculine expression in men. While framed as a movement toward inclusivity and freedom of identity, this phenomenon carries potential risks of eroding Islamic religious values and destabilizing social balance (tawazun) as protected by Sharia through its primary sources: the Qur’an, Hadith, and Fiqh. Such disruption has broader implications for weakening the family institution, which functions as a fundamental social pillar in Islam. The shift in gender expression is viewed as a direct challenge to the principle of dharuriyat in Islamic jurisprudence, particularly with respect to hifz al-nasl (protection of lineage), hifz al-nafs (protection of life), and hifz al-din (protection of religion). Furthermore, it raises concerns of moral decadence in contemporary society. The research employs a qualitative descriptive method with a literature-based approach, drawing upon classical and modern Islamic legal scholarship, contemporary studies on non-binary gender identities, sociological reports, and other relevant academic sources. Data are analyzed through the conceptual framework of Maqasid al-Sharia, which provides both normative and contextual insights. The findings reveal a paradigm bias that blurs the distinction between biological sex and socially constructed gender. In Islamic thought, sex is an innate and divinely ordained attribute, while gender roles are understood as differentiated yet complementary expressions of masculinity and femininity. From the perspective of Maqasid al-Sharia, maintaining the integrity of gender expression in accordance with human fitrah is classified as a dharuriyat necessity, essential for sustaining moral order, protecting the family, and ensuring long-term social stability.